Gentiopicroside Ameliorates Diabetic Renal Tubulointerstitial Fibrosis via Inhibiting the AT1R/CK2/NF-κB Pathway - Xu, Zhanchi; Zhang, Meng; Wang, Yu; Chen, Rui; Xu, Shiyue; Sun, Xiaohong; Yang, Yan; Lin, Zeyuan; Wang, Shaogui; Huang, Heqing (Frontiers in Pharmacology, 2022)
Renal tubulointerstitial fibrosis (TIF), characterized by epithelial-to-mesenchymal transition (EMT) of renal tubular epithelial cells, is the typical pathological alteration in diabetic nephropathy. Gentiopicroside (GPS), a nature compound with anti-inflammatory activity, has been demonstrated to alleviate glomerulosclerosis. Whereas, whether GPS inhibit TIF via regulating inflammation remains unclear. In this study, diabetic db/db mice and high glucose (HG)-stimulated renal tubular epithelial cells (NRK-52E) were applied to explore the effects and mechanisms of GPS on TIF. The results in vivo showed that GPS effectively improve glycolipid metabolism disorder, renal dysfunction and TIF. Specially, GPS treatment reversed the abnormal expressions of EMT marker proteins including elevated α-smooth muscle actin and Vimentin and decreased Eadherin in the kidney of db/db mice. Meanwhile, GPS treatment also inhibited protein expressions of angiotensinⅡ type 1 receptor (AT1R) and CK2α and the activation of NF-κB pathway. Moreover, above effects of GPS acted in vivo were further obeserved in vitro in HG-stimulated NRK-52E cells, which were independent on its effects on glucose and lipid lowering but were reversed by AT1R over-expression. Together, our results indicate that GPS that directly inhibits CK2/NF-κB inflammatory singaling pathway via AT1R may also contribute to the amelioration of TIF in diabetes.